Solution representations for Trefftz-type finite elements - Piltner, Reinhard (Computer Assisted Methods in Engineering and Science; Vol 10 No 4 (2003), 2023)
Solution representations are available for several differential equations. For elasticity problems some of the solution representations are considered in this paper. The solution representations can be used for a systematic construction of Trefftz functions for the derivation of Trefftz-type finite elements. For the example of a thick plate a set of Trefftz functions is presented.